Invisibilidade do racismo no Brasil: nas práticas escolares, culturais e sociais da discriminação racial (Pós Lei 10.639) - (:unkn) unknown (Universidade Federal de Goiás, 2017)
This dissertation investigates situations of racism and discrimination in Brazil, as well as the process of invisibility of these cases in the country. In the Brazilian society racism is ignored and is often taken as a joke, transforming the negro in Algoz. In school these practices also occur as a reflection of society. With the aim of reducing these situations arose the Law 10.639/03 which determines the compulsory teaching of history and culture african and afro-brazilian. Fourteen years after the creation of the Law 10.639/2003 will be analyzed two collections made available by the National Program of textbook for the triennium 2017-2019, in order to investigate how the negro is represented in the textbook after the law and investigate whether the book comprises the expectations of Learning Reference Curriculum of the State Network of Education of Goiás. Will be investigated also the public policies created in Brazil, with the aim of remedying the inequalities between whites and blacks.
Invisibility of racism in Brazil: in school practices, cultural and social aspects of racial discrimination (Law 10,639)
Keywords: Negros; Lei 10.639/2003; Racismo; Educação; Black; Law 10.639/2003; Racism; Education; CIENCIAS HUMANAS::HISTORIA